Convalescent Plasma: An Old Trick for the Treatment of COVID-19 - Reza Jafari; Sajjad Ranjbar Kouchaksaraei; Reza Farid Hosseini; Mehrnaz Nayeb; Alireza Ranjbar (Mazandaran University of Medical Sciences, 2020)
This article has no abstract.